FOOD AND NUTRITION AS PART OF THE TOTAL PAIN CONCEPT IN PALLIATIVE CARE - Pinho-Reis,Cíntia (2022)
ABSTRACT Total pain is an essential concept in palliative care and so it is food and nutrition. During the disease progression, patients’ food and nutrition become very often altered and patients are faced with many losses related to the feeding process. These losses can range from the incapacity to taste, swallow, chew, digest and absorb nutrients properly to the loss of the patient’s ability to eat with autonomy, to manage cutlery and to use the oral route which may culminate in depression and social isolation. Many palliative care patients also present eating-related symptoms, involuntary weight loss, and food refusal. Mostly in the end-of-life phase spiritual issues related to food and nutrition may also emerge. All these issues interfere with daily family life and with patients’ comfort and quality of life affecting all the patients’ human being dimensions - physical, psychological, social, and spiritual - and contributing to patients’ total pain.